A low-cost novel lateral flow nucleic acid assay (LFNAA) for yak milk authentication. (March 2020) - Wang, Zhiying; Li, Tingting; Yu, Wenjie; Qiao, Lu; Yang, Shuming; Chen, Ailiang
Abstract: A low-cost novel lateral flow nucleic acid assay (LFNAA) was developed for rapid and sensitive authentication of yak milk on-site. In this method, a special abasic spacer C3 and tail nucleotide sequence modified reverse primers were innovatively designed for rapid isothermal recombinant polymerase amplification (RPA) to obtain a double-stranded amplicon with a single-stranded DNA tail, which could directly bind to gold nanoparticle (AuNP)-labeled detection probes, and produce a sandwich complex to show a red color on the test line of the strip. Compared to conventional RPA-lateral flow assay based on expensive antibodies, the proposed method in this work demonstrated massive cost reduction, avoided time-consuming and laborious AuNP-antibody conjugation process. The LFNAA revealed high specificity and sensitivity, which allowed detecting as low as 5% of yak milk within 40 min. This LFNAA facilitated non-specialized operators to field determine the authenticity of yak milk by naked eyes, and could be readily applied to other nucleic acid detection such as food safety inspection and point-of-care medical tests. Highlights: A low-cost RPA-based LFNAA was developed for yak milk authentication. A special spacer C3 and tail were innovatively modified reverse primers for RPA. This design could obtain a double-stranded amplicon with a single-stranded DNA tail. The LFNAA show the same sensitivity as agarose gel and 5% yak milk could be detected. The LFNAA could be observed by non-professional operators within 40 min at 37–40 °C.